Podcast-integrated speaking instruction: Enhancing informal digital learning of English, academic engagement, and speaking skills - Lei Peng; Shamim Akhter; Arash Hashemifardnia (Acta Psychologica, 2025)
The incorporation of digital technologies in language education has become increasingly prevalent, providing innovative methods for developing speaking competencies and increasing learner motivation. Among these technological tools, podcasts have emerged as particularly valuable resources, offering both accessibility and authentic language exposure. However, despite their potential, empirical research examining their systematic pedagogical application remains limited. This study examined the effects of structured podcast-based speaking instruction on three key dimensions: Informal Digital Learning of English (IDLE), academic engagement (AE), and speaking skills. The research involved seventy female intermediate-level EFL students at a private language institute in Iran. Using a pretest-posttest control group design, the participants were randomly assigned to either an experimental group (EG, n = 35) that received seventeen sessions of podcast-integrated instruction over eight weeks, or a control group (CG, n = 35) that followed standard speaking instruction. Data collection involved validated questionnaires measuring IDLE and AE, along with pre- and post-intervention speaking assessments evaluated through a standardized rubric. A one-way analysis of Covariance (ANCOVA) was employed to compare group outcomes while accounting for baseline differences. Results indicated that the EG demonstrated significantly greater improvement across all measures - speaking skills, IDLE engagement, and AE - compared to the CG. These findings offer important implications for EFL pedagogy, suggesting that carefully designed podcast activities can serve as an effective tool not only for enhancing speaking skills but also for fostering academic motivation and promoting autonomous learning behaviors.